How did Ontario healthcare institutions implement and legitimize Covid-19 vaccine mandates? A qualitative multi‑method study protocol - Claudia Chaufan (PLoS ONE, 2025)
Background Upon the WHO declaration of Covid-19 as a pandemic, healthcare workers (HCWs) – unvaccinated by necessity – were celebrated as “heroes” for their service under difficult conditions. Later, as some of them resisted vaccine mandates, they were reframed as “threats”, regardless of personal behaviour, workplace setting, or evidence of their harmfulness. This discursive shift and the institutional mechanisms supporting it remain underexamined. Goal This protocol outlines a qualitative multi‑method study investigating the implementation of Covid-19 vaccine mandates in medical establishments across Ontario, Canada. Methods This qualitative multi‑method planned study includes two phases. Phase 1 is an environmental scan of institutional vaccine mandate policies across a purposive sample of diverse Ontario medical establishments. It will track policy implementation timelines, mandates scope, exemptions eligibility criteria, and supporting scientific evidence presented. Phase 2 is a critical interpretive analysis of documents collected in Phase 1 that draws on Max Weber’s theory of bureaucracy and legitimacy, Carol Bacchi’s “What Is the Problem Represented to Be” (WPR) approach, and Brian Martin’s framework on suppression of dissent to identify patterns in the institutional framing and treatment of challenges to mandated vaccination. Expected outcomes The study outlined in this protocol is expected to yield descriptive and interpretive insights into how bureaucratic structures shaped mandate enforcement and dissent suppression. Results are expected to inform academic debates on institutional legitimacy, governance, and public health ethics.